A new inertial-projection algorithm for approximating common solution of variational inequality and fixed point problems of multivalued mappings - Owolabi, Abd-semii Oluwatosin-Enitan; Alakoya, Timilehin Opeyemi; Taiwo, Adeolu; Mewomo, Oluwatosin Temitope (Numerical algebra, control and optimization, 2022)
In this paper, we present a new modified self-adaptive inertial subgradient extragradient algorithm in which the two projections are made onto some half spaces. Moreover, under mild conditions, we obtain a strong convergence of the sequence generated by our proposed algorithm for approximating a common solution of variational inequality problem and common fixed point of a finite family of demicontractive mappings in a real Hilbert space. The main advantages of our algorithm are: strong convergence result obtained without prior knowledge of the Lipschitz constant of the related monotone operator, the two projections made onto some half-spaces and the inertial technique which speeds up rate of convergence. Finally, we present an application and a numerical example to illustrate the usefulness and applicability of our algorithm.